(untitled) (Signifiances (Signifying), 2019)
Is the linguistic sign, traditionally conceived as a symbol (from the Greek sym + bol ‘putting two faces together’), diabolical (from the Greek dia ’to separate’)? That is the question arised by this second issue of Signifiances, which proposes questioning the duplicity or, more exactly, the duplicities of the sign. The articles presented emanate from researchers from various theoretical horizons; but the studies gathered here bear witness to the same concern: the desire to question, to challenge, what is usually considered as given. All the terms of the definition of the sign as an arbitrary union of a signifier and a signified, symbolizing a portion of reality, are here questioned, each paper being particularly interested in this or that aspect of this conception. The elements of the definition are not seen as objects with a positive existence but rather as dynamic processes (speaker experience) or as the result of constitutive points of view of linguistic entities (biased linguist), and most of the contributions are based on the signifier as a dynamic process.